2018
DOI: 10.1016/j.jcyt.2017.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Mineralization by mesenchymal stromal cells is variously modulated depending on commercial platelet lysate preparations

Abstract: Despite the standardized procedures applied to obtain commercial hPL, this study highlights the divergent effects of different preparations and emphasizes the importance of cellular ontology, donor age and cell proliferative capacity to optimize the osteogenic induction capabilities of mesenchymal stromal cells and design more effective cell-based therapeutic protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…This discrepancy persists when comparing the absolute results of alizarin red staining and ALP activity measurement: in alizarin red staining, the hPL groups showed calcium content higher than or as high as the FCS groups while ALP activity varies more, especially when comparing H1 and F10 groups, where the F10 group presents higher ALP activity throughout differentiation from day seven onwards. For the pairs of H1 vs. F1 and H10 vs. F10, the previously described statement of superiority or equality of the hPL [16,17,[21][22][23][24][26][27][28]31] is still valid.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…This discrepancy persists when comparing the absolute results of alizarin red staining and ALP activity measurement: in alizarin red staining, the hPL groups showed calcium content higher than or as high as the FCS groups while ALP activity varies more, especially when comparing H1 and F10 groups, where the F10 group presents higher ALP activity throughout differentiation from day seven onwards. For the pairs of H1 vs. F1 and H10 vs. F10, the previously described statement of superiority or equality of the hPL [16,17,[21][22][23][24][26][27][28]31] is still valid.…”
Section: Discussionmentioning
confidence: 92%
“…Several studies evaluated BMSC differentiation potential after cell expansion in hPL-containing medium, while the differentiation medium itself contained only FCS as a supplement [17,18,22,23,[28][29][30]. There have also been multiple studies reporting that hPL does not affect osteogenic differentiation [16,17,21,22,24,[27][28][29]31] or even increases the osteogenic differentiation potential of BMSC [22,23,25,26]. However, it remains unclear how hPL as a part of an osteogenic differentiation medium (ODM) influences the kinetics of the osteogenic differentiation of BMSC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have reported differences in MSC proliferation and osteogenic differentiation when cultured in different HPL formulations, expressing differences in their protein compositions [ 15 , 73 ]. MSC proliferation, i.e., PD rate/time, is considered a “key parameter” during ex vivo expansion [ 11 ], and ALP and mineralization assays are routinely used to test the in vitro osteogenic capacity of MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of BTE, a recent study demonstrated differential effects of commercial HPL products on the mineralization capacity of BMSCs, although the mechanisms and HPL components contributing to these differences were not studied [ 15 ]. It would be of interest to investigate the effects of PC storage times on the cytokine contents of HPL, and subsequently the proliferation kinetics and osteogenic differentiation potential of HPL-expanded MSCs.…”
Section: Introductionmentioning
confidence: 99%